A suitable mechanism for the interconnection phase of temporary coupling of adjacent microgrids - Bourbour, S.; Shahnia, Farhad (2016)
© 2016 IEEE. A microgrid is supposed to supply its demand self-sufficiently. However, the generation intermittency and load variations can result in the impermanent overloading of the microgrid. This can be addressed by allowing the microgrid to import some power from one or more adjacent microgrids, after their short interconnection. The transition phase of forming a system of coupled microgrids is focused in this paper, and a suitable mechanism is proposed which enables the interconnection of the microgrids after a proper synchronization. The performance of the proposed mechanism is evaluated by PSCAD/EMTDC-based time-domain simulation studies.